Endocytosis is required for Toll signaling and shaping of the Dorsal/NF-κB morphogen gradient during Drosophila embryogenesis - Lund, Viktor K. (National Academy of Sciences, 2010)
Dorsoventral cell fate in the Drosophila embryo is specified by activation of the Toll receptor, leading to a ventral-to-dorsal gradient across nuclei of the NF-κB transcription factor Dorsal. Toll receptor has been investigated genetically, molecularly, and immunohistologically, but much less is known about its dynamics in living embryos. Using live imaging of fluorescent protein chimeras, we find that Toll is recruited from the plasma membrane to Rab5(+) early endosomes. The distribution of a constitutively active form of Toll, Toll(10b), is shifted from the plasma membrane to early endosomes. Inhibition of endocytosis on the ventral side of the embryo attenuates Toll signaling ventrally and causes Dorsal to accumulate on the dorsal side of the embryo, essentially inverting the dorsal/ventral axis. Conversely, enhancing endocytosis laterally greatly potentiates Toll signaling locally, altering the shape of the Dorsal gradient. Photoactivation and fluorescence recovery after photobleaching studies reveal that Toll exhibits extremely limited lateral diffusion within the plasma membrane, whereas Toll is highly compartmentalized in endosomes. When endocytosis is blocked ventrally, creating an ectopic dorsal signaling center, Toll is preferentially endocytosed at the ectopic signaling center. We propose that Toll signals from an endocytic compartment rather than the plasma membrane. Our studies reveal that endocytosis plays a pivotal role in the spatial regulation of Toll receptor activation and signaling and in the correct shaping of the nuclear Dorsal concentration gradient.